Sosialisasi Penguatan Moderasi Beragama pada Anggota Karang Taruna di Desa Mekar Buana, Kabupaten Karawang - Ajat Sudrajat; Vidya Arisandi; Dwi Yani Salsabilah; Aninisa Alfa; Cindy Endah Sari (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This service is an initiative taken by the volunteers to educate the community, particularly the youth of Karang Taruna in the village of Mekar Buana in Karawang. The objective is to create awareness among the youth of Karang Taruna about religious diversity. The lectures and interviews are the primary methods of implementation. The activity was conducted successfully, and the results and discussions showed that the youth of the organization now have a better understanding of religious moderation. In conclusion, this service has helped to enlighten the youth about religious life, particularly the importance of religious moderation.